Patients’ opinions of food and mealtimes in hospital. - Behrens, Rachel (2012)
Background: Malnutrition impacts many patients in hospital and can have serious consequences. This study aims to obtain patients’ opinions relating to food and mealtimes to gain further understanding of factors which influence levels of nutrition in hospital. Findings were compared with existing nutritional policies and best practice indicators, established to provide high standards of nutritional care and hereby influence nutritional status during a hospital stay. Method: 11 semi-structured interviews were conducted with older patients from a medical ward in a Midlands hospital; opinions of various aspects of food and mealtimes were recorded. Findings: Four key themes emerged about the food in hospital and mealtime experience, relating to food intake; food, environment, mealtimes and appetite. Implications for practice: Most participants were satisfied with food, choice and environment. There are areas where policy has not translated effectively into practice and indicators are not being met, for example; inappropriate temperature of meals and too large portion sizes. Other themes were recognised to decrease participants’ appetite in hospital, which could significantly affect nutritional intake. Suggestions for improvements based on this study would be; providing patients with choice of portion-size, introducing alternative mealtime environments and increasing daily exercise. The relevance of the findings are limited by small size of the study and single ward representation.